Decellularized Periodontal Ligament Cell Sheets with Recellularization Potential. (December 2014) - Farag, A.; Vaquette, C.; Theodoropoulos, C.; Hamlet, S.M.; Hutmacher, D.W.; Ivanovski, S.
The periodontal ligament is the key tissue facilitating periodontal regeneration. This study aimed to fabricate decellularized human periodontal ligament cell sheets for subsequent periodontal tissue engineering applications. The decellularization protocol involved the transfer of intact human periodontal ligament cell sheets onto melt electrospun polycaprolactone membranes and subsequent bi-directional perfusion with NH4 OH/Triton X-100 and DNase solutions. The protocol was shown to remove 92% of DNA content. The structural integrity of the decellularized cell sheets was confirmed by a collagen quantification assay, immunostaining of human collagen type I and fibronectin, and scanning electron microscopy. ELISA was used to demonstrate the presence of residual basic fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF), and hepatocyte growth factor (HGF) in the decellularized cell sheet constructs. The decellularized cell sheets were shown to have the ability to support recellularization by allogenic human periodontal ligament cells. This study describes the fabrication of decellularized periodontal ligament cell sheets that retain an intact extracellular matrix and resident growth factors and can support repopulation by allogenic cells. The decellularized hPDL cell sheet concept has the potential to be utilized in future "off-the-shelf" periodontal tissue engineering strategies.